Correlation of Burnout and Selfefficacy in Employees Working in Special Education Structures - Νιθαυριανάκη, Aσπασία; Παπαδούρης, Παναγιώτης (Education Sciences, 2020)
The present study investigates the relationship between burnout and perceived self-efficacy of professionals in the Greek Special Education sector. The survey involved 157 teachers of various specializations as well as welfare and pupil support staff working in public structures of Special Education in West Attica. Data collection was conducted through a tool resulted from the synthesis of The Maslach Burnout and Copenhagen Burnout Inventories and the Norwegian Teachers’ Sense of Efficacy Scale. Results reveal moderate degree of burnout in participants’ personal life and emotional exhaustion, low degree of depersonalization and high degree of the sense of personal accomplishment and self-efficacy. Multiple regression analysis and structural equation modeling results showed that self-efficacy plays a significant role in predicting all dimensions of burnout.